Konsep Kritik Matan: Sejarah, Tujuan, Manfaat, dan Langkah – Langkah Penelitian Matan Hadis - Jailuddin, Syuaib (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The criticism of hadith texts is a discipline in the study of hadith that aims to test the validity and authenticity of hadith texts, both in terms of sanad and matan. The concept of this criticism is rooted in the term